Platelet Adhesion to Fibrinogen, Fibrin Monomer, and Fibrin Protofibrils in Flowing Blood - The Effect of Fibrinogen Immobilization and Fibrin Formation - Jiroušková, Markéta; Dyr, Jan Evangelista; Suttnar, Jiří; Holada, Karel; Trnková, Bohuslava (Thrombosis and Haemostasis, 1997)
Platelet fibrin(ogen) adhesive interactions were investigated in whole citrated blood using the rectangular perfusion chamber at wall shear rates of 300 and 1600s1 with regard to the amount and structure of immobilized protein. Only single platelets adhered to adsorbed fibrinogen at both low and high surface fibrinogen concentrations and at 1600 s1 almost no adhesion was observed. When using spray-immobilized protein, platelet adhesion was significantly higher than to ad sorbed protein. Conversion of adsorbed fibrinogen to fibrin monomer resulted in the formation of pronounced platelets aggregates and with the elevation of wall shear rate 50% decrease of adhesion took place. Degree of platelet adhesion to fibrin monomer was significantly influenced by immobilized protein concentration at both shear rates. However, the morphology (small and dense platelet aggregates) and extent of platelets adhered to fibrin pentamer was nearly the same at both shear rates. Starting with surface-bound fibrinogen and alternating addition of thrombin and fibrinogen fibrin pentamer was prepared using the stepwise synthesis. This methodology is based on the observation that at low concentration immobilized fibrin monomer binds fibrinogen in 1:1 molar ratio. The gradually formed fibrin of a defined size and composition can be a useful tool in the further understanding of the role of fibrin architecture in the pathophysiology of thrombosis.